Analisis Nilai-Nilai Pendidikan Karakter pada Animasi Nussa dan Rara Episode Nussa Bisa - Maulida, Nabila; Abidin, Zainal; Iqbal, Muhammad; Sari, Rita (Mulya Literasi Publishing, 2023)
The purpose of this study is to analyze the character education values contained in the animation of Nussa and Rara’s episode of Nussa Bisa. The type of research is library research. The results of the analysis are guided by the values of character education according to the Ministry of National Education in 2011. Of the 18-character education values, there are 12 characters that appear in the animation of Nussa and Rara episode of Nussa Bisa. The 12 characteristics are religion, responsibility, respect for fellow religious people, curiosity, respect for the work and achievements of others, caring, thinking logically, critically, creatively, and innovatively, love for the environment, hard work, and taking risks. So, from this literature study search, it can be concluded that the animation of Nussa and Rara is very worthy of being a spectacle for MI/SD-age children because it teaches many noble ethical values that can be instilled early.